Long-acting growth hormones: innovations in treatment and guidance on patient selection in pediatric growth hormone deficiency - Chiara Rodaro; Gianluca Tamaro; Elena Faleschini; Gianluca Tornese (Annals of Pediatric Endocrinology & Metabolism)
Long-acting growth hormones (LAGHs) represent a significant advancement in the treatment of pediatric GH deficiency, offering an alternative to daily recombinant human GH (rhGH) therapy. Traditional rhGH treatments, although effective, require daily injections, often leading to poor adherence due to the frequency of dosing, injection pain, and difficulties with storage and travel. In contrast, LAGHs, such as somatrogon, somapacitan, and lonapegsomatropin, are designed for once-weekly administration, improving patient compliance and quality of life. LAGHs have demonstrated non-inferiority to daily rhGHs in phase 3 clinical trials, showing similar efficacy in terms of growth velocity and safety profiles. Despite these advantages, concerns remain regarding the altered pharmacodynamics of LAGHs such as the lack of pulsatile secretion and potential for antibody formation. Although the overall safety of LAGHs has been confirmed, side effects, such as lipoatrophy at the injection site, may occur, especially with PEGylated formulations. Guidelines for prescribing LAGHs are currently evolving. LAGHs are not yet approved for other conditions traditionally treated with rhGHs, such as Turner or Noonan syndrome. Pediatric endocrinologists should carefully consider which patient groups would benefit most from this therapy, particularly individuals at risk of poor adherence to daily injections such as patients undergoing multidrug therapy, patients with needle phobia or behavioral disorders, very young children, adolescents, patients with separated parents, families that travel frequently, or children involved in activities such as scouting. LAGHs present an opportunity to enhance therapeutic outcomes and adherence, but careful patient selection remains critical to maximize their potential benefits.